Spelling What You Hear: Investigating The Role of Pronunciation in English Spelling Difficulties - Ray, Nurul Anisya; Rambe, Tiara Fadiyah; Raihani, Raihani; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This research investigates how pronunciation relates to spelling performance among English language learners, focusing on the role of phonological awareness in shaping their spelling behaviors and mistakes. Employing a descriptive qualitative method, the study involved six Indonesian university students majoring in English, who responded to a ten-item online questionnaire. The results indicate that learners frequently depend on how words are pronounced when trying to spell them. While this approach may work for regular words, it often causes errors in cases involving silent letters or irregular spellings, such as in knife, receipt, and colonel. Although participants demonstrated some awareness of these inconsistencies, their strong reliance on phonological strategies contributed to typical mistakes, including omitting silent letters or confusing similar-sounding words. These findings imply that pronunciation-based strategies alone are not sufficient for accurate spelling in English. Therefore, English instruction should include focused teaching on spelling conventions, morphological elements, and visual recognition of word patterns. Such an approach is expected to enhance learners’ spelling accuracy and minimize confusion resulting from the unpredictable nature of English orthography.